Budulínek and Labyrinth - Bernard, Jan (Iluminace, 2021)
Artist, photographer, writer and theorist Václav Zykmund (June 18, 1914 - May 10, 1984) was one of the younger representatives of pre-war and post-war Czech surrealism. He is the founder of two important art groups Ra (1944) and Parabola (1963). His work was influenced by Josef Šíma, Salvator Dalí, Man Ray and André Breton. His close friend was the leading theorist Karel Teige, who led him to surrealism. Zykmund was a communist, but in the period of socialist realism he defended modern art from ideological criticism. Twice in his life he resorted to filmmaking. During the political trials and other repressions of 1949-1953, he became an artist and director of cartoons and puppet films in Brno, which he created together with his girlfriend and later his wife Anna Veselá-Korečková. They contributed to the development of Czech animated film for children in the period of the beginning of the work of Jiří Trnka, Hermína Týrlová, Karel Zeman, Zdeněk Miller and Břetislav Pojar. At the time of normalization after the Soviet invasion of Czechoslovakia, Zykmund was first expelled from the Communist Party, and from 1972 he was banned from public teaching, theory, and art. In financial need he sold a drawing donated to him by Max Ernst and for the money he earned he bought a Super 8mm camera and projector. The present study is based on an analysis of animated films preserved in the National Film Archive and private films preserved in his estate.
Keywords: Václav Zykmund; surrealism; animation; amateur film; normalisation; lettrism